Long‐term outcome of the use of intravesical botulinum toxin for the treatment of overactive bladder (OAB) - Mohee, Amar; Khan, Ayisha; Harris, Neil; Eardley, Ian (BJU international, 2013)
What's known on the subject? and What does the study add? It is known that intravesical botulinum toxin (BT) is an effective treatment for overactive bladder, especially in the patients with neurogenic detrusor overactivity. Several studies have shown that diagnostic and health‐related quality of life parameters improve after intravesical BT treatment. The present study has the merit of reporting a ‘real‐life’ experience in a large teaching hospital in the UK National Health Service. As opposed to controlled trials, this retrospective study based largely on patient choice, shows that most patients fail to persist with intravesical BT treatment, mainly due to tolerability issues. Objectives To assess the long‐term compliance with repeated injections of intravesical botulinum toxin (BT) in a ‘real‐life’ mixed population of patients with idiopathic detrusor overactivity and neurogenic detrusor overactivity. To identify the reasons why patients discontinued BT therapy and to explore the outcomes of those patients who did discontinue treatment. Patients and Methods Retrospective evaluation of the case notes of a series of patients who had received intravesical BT treatment at a large UK teaching hospital. No antibiotic prophylaxis was given for the procedure. Results Over a period of 7 years, 268 patients were initiated on intravesical BT treatment for overactive bladder (OAB) at our institution, with 137 followed up for ≥36 months, with 80 patients having ≥60 months follow‐up after their first injection. Almost two‐thirds of patients (61.3%) had discontinued intravesical BT therapy at 36 months, with a 63.8% discontinuation rate at 60 months. The main reasons for discontinuation were tolerability issues, mainly urinary tract infections and the need for clean intermittent self‐catheterisation. Primary and secondary losses of efficacy were of secondary importance. Most of the patients that discontinued have remained under urology care and now receive alternative methods of treatment. Conclusions Intravesical BT therapy is an effective short‐term treatment for OAB. With time, two‐thirds of patients discontinued treatment usually because of the tolerability issues associated with treatment.